Discovering a new fossil chironomid from Lower Cretaceous Lebanese Amber: Electroneura pinhoi sp. nov. Amaral, Silva & Baranov (Chironomidae: Tanypodinae) - Fabio Laurindo da Silva; André P. Amaral; Dany Azar; Viktor Baranov (PalZ, 2024)
Here we present new insights into Chironomidae (Insecta, Diptera) preserved in Lower Cretaceous Lebanese amber. We describe a new genus and species, Electroneura pinhoi gen. et sp. nov., seemingly related to Tanypodinae and offer an amended description of Libanopelopia cretacica Veltz, Azar and Nel, 2007. Moreover, our investigation highlights the challenges of assigning fossils to modern taxonomic groups, based on previous studies of Tanypodinae, underscoring the necessity of considering the geological context and utilizing, when possible, both morphological and molecular data from extant taxa to validate taxonomic assignments in paleontological studies.